2022
DOI: 10.1155/2022/8440019
|View full text |Cite
|
Sign up to set email alerts
|

Nephroprotective Effect of Asparagus africanus Lam. Root Extract against Gentamicin-Induced Nephrotoxicity in Swiss Albino Mice

Abstract: The kidney is the organ most vulnerable to nephrotoxic drugs such as gentamicin. Nephrotoxicity is a rapid deterioration of kidney function due to various factors. Gentamicin causes nephrotoxicity, which was manifested by an increase in serum kidney biomarkers. Asparagus africanus is one of the ethnomedicinal plants used as traditional medicine for treating various ailments, including kidney disease in Ethiopian society. Thus, the aim of this study is to evaluate the nephroprotective effect of A. africanus roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…This finding is congruent with the results of a study conducted in Ethiopia on gentamicin-induced mice. 63 Furthermore, the increased in serum creatinine and blood urea levels due to gentamicin injection was remarkably reduced by the administration of methanol leaf extract of Ajuga remota , which is in line with the results of previous studies of different medicinal plants performed on gentamicin-induced mice. 64–66 The current study also found significantly decreased mean serum creatinine and blood urea levels in MEAR-treated mice.…”
Section: Discussionsupporting
confidence: 88%
“…This finding is congruent with the results of a study conducted in Ethiopia on gentamicin-induced mice. 63 Furthermore, the increased in serum creatinine and blood urea levels due to gentamicin injection was remarkably reduced by the administration of methanol leaf extract of Ajuga remota , which is in line with the results of previous studies of different medicinal plants performed on gentamicin-induced mice. 64–66 The current study also found significantly decreased mean serum creatinine and blood urea levels in MEAR-treated mice.…”
Section: Discussionsupporting
confidence: 88%
“…The TPC of the A. corrorima hydro distillation extract was 3.98 ± 0.27 mg GAE/g for the seed and 1.32 ± 0.07 mg GAE/g for the pod [ 17 ]. The disagreement might be due to the method of extraction, the solvent used, the plant seed harvesting period, the different geographical distribution of the plant, and other environmental factors [ 23 ]. The principal antioxidants or free radical scavengers in plants are correlated with phenolic compounds [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The solvent extracts were filtered and concentrated using a rotary evaporator at a temperature of 60 °C with a speed of 90 rpm to have a solid consistency and dried at room temperature. Finally, the crude extract was packed in air-tight glass bottles with proper labels and kept in a refrigerator at 4 °C until used for the next experiment [ 23 ]. The qualitative phytochemical screening of the plant crude extracts such as saponin, alkaloids, steroid, tannins, flavonoids, phenolic, terpenoids, glycosides and quinones were investigated using a standard methods reported from the previous similar study [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Aminoglycosides including gentamicin has been listed as a category of antibiotics with murderous effects against aerobic bacteria. One of the known side effects of these antibiotics is nephrotoxicity (Meka Kedir et al, 2022). The toxic impacts of aminoglycosides antibiotics on kidney are imagined to be due to the induction of the generation of free radicals (Pakfetrat et al, 2022).…”
Section: Effect On Urinary Systemmentioning
confidence: 99%